2015
DOI: 10.1111/cmi.12417
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear trafficking, histone cleavage and induction of apoptosis by the meningococcal App and MspA autotransporters

Abstract: Summary N eisseria meningitidis, a major cause of bacterial meningitis and septicaemia, secretes multiple virulence factors, including the adhesion and penetration protein (App) and meningococcal serine protease A (MspA). Both are conserved, immunogenic, type Va autotransporters harbouring S6‐family serine endopeptidase domains. Previous work suggested that both could mediate adherence to human cells, but their precise contribution to meningococcal pathogenesis was unclear. Here, we confirm that App and MspA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…App and MspA are internalized by human cells and traffic to the nucleus. In vitro, MspA and App proteolytically cleave histone H3, and in vivo, they induce a dose-dependent increase in dendritic cell death via caspase-dependent apoptosis [100]. However, the functional link between these properties remains to be clarified.…”
Section: Nucleomodulins Acting As Proteasesmentioning
confidence: 99%
“…App and MspA are internalized by human cells and traffic to the nucleus. In vitro, MspA and App proteolytically cleave histone H3, and in vivo, they induce a dose-dependent increase in dendritic cell death via caspase-dependent apoptosis [100]. However, the functional link between these properties remains to be clarified.…”
Section: Nucleomodulins Acting As Proteasesmentioning
confidence: 99%
“…A HiTrap column pre-packed with five milliliters of Sephadex G-25 Superfine (GE Healthcare Lifesciences) equilibrated with 5 column volumes of phosphate buffered saline (PBS) was used for buffer exchange. His6-tagged recombinant E. coli trigger factor protein (rTF), encoded by the plasmid pCold TF (Takara Bio), was purified as previously described [18]. Protein concentration was measured using the Pierce BCA protein assay kit (Thermo Fisher Scientific) following endotoxin removal using Pierce High Capacity Endotoxin removal spin columns (Thermo Fisher Scientific).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Alternatively proteins were transferred to nitrocellulose membranes and probed with rabbit polyclonal anti-NalP [6] or mouse anti-pentahistidine antibody (Qiagen) diluted 1:5,000 or 1:2,000, respectively, in blocking buffer (5% anti-mycotic solution. Dendritic cells were generated as previously [18], and subsequently grown in RPMI (Sigma) supplemented with 10% FBS and 1% antibiotic / anti-mycotic. Human brain (cerebral cortex) astrocytes (ScienCell) were cultured in astrocyte growth medium supplemented with 5% FBS, 1 × astrocyte growth supplement and 1% antibiotic / anti-mycotic.…”
Section: Sds-page and Immunoblot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The process by which these steps occur is incompletely understood (Sokolova et al , 2004, Yazdankhah et al , 2004, Hill et al , 2010), but identified meningococcal adhesins include components of the type IV pilus (PilC1, PilC2 and PilQ), the outer membrane proteins Opa, Opc, Factor H-binding protein, PorA, PorB, HrpA, NadA, App and MspA, as well as lipooligosaccharide (LOS) (Merz et al , 2000, Hadi et al , 2001, Turner et al , 2006, Morand et al , 2009). Host cell receptors that have been identified include alpha actinin, integrins, CEACAMS, CD46, Complement receptor 3, GP96 scavenger receptor, laminin, platelet-activating factor, mannose receptor, Transferrin receptor 1, Laminin receptor and Galectin-3 (Merz et al , 2000, Morand et al , 2009, Orihuela et al , 2009, Quattroni et al , 2012, Alqahtani et al , 2014, Khairalla et al , 2015).…”
Section: Introductionmentioning
confidence: 99%